PROBLEMS OF ADJUSTING THE "INDEPENDENCE CURRICULUM" LEARNING SYSTEM AT SMP NEGERI 2 PONTIANAK - Hadi Wiyono (Jurnal Scientia, 2023)
This study aims to find out the learning system and adjustments in implementation of the independent curriculum at SMPN 2 Pontianak, in preparation for the implementation of the independent curriculum by SMPN 2 Pontianak teachers who have been given directions from the school so that teachers follow the driving teacher program before implementing the independent curriculum in order to support teacher readiness. in implementing the independent curriculum learning system. In the implementation of learning, teachers find obstacles to the use of technology in the learning process, including the method of solving problems in textbooks that are still conventional and less varied which can cause student boredom, besides that the use of the independent learning platform has not been used optimally by teachers, even though there are many things that can be used to support learning. The qualitative research method is a descriptive approach through observation, interview and documentation techniques in obtaining data about the independent curriculum learning system at SMPN 2 Pontianak and the obstacles and teachers' efforts to overcome these obstacles. The results of this study are the learning system at SMPN 2 Pontianak with 70% regular or routine learning and 30% project activities.The thing that has the most influence on the independent curriculum is the learning schedule. Then in learning there is still minimal use of technology, the completion of questions in textbooks is still less varied, there is still a lack of literacy for learning through the independent learning platform, finally, on teacher competence which is still low and needs to be improved based on information from the vice principal of SMPN 2 Pontianak.